Activation of Orexin 1 Receptors in the Paraventricular Nucleus Contributes to the Development of Deoxycorticosterone Acetate-Salt Hypertension Through Regulation of Vasopressin - Bigalke, Jeremy A.; Gao, Huanjia; Chen, Qing-Hui; Shan, Zhiying (Frontiers in Physiology, 2021)
Salt-sensitivity is a major factor in the development of hypertension. The brain orexin system has been observed to play a role in numerous hypertensive animal models. However, orexin’s role in the pathology of salt-sensitive hypertension (SSH) remains to be adequately explored. We assessed the impact of orexin hyperactivity in the pathogenesis of the Deoxycorticosterone Acetate (DOCA) - salt rat model, specifically through modulation of Arginine Vasopressin (AVP). Adult male rats were separated into three groups: vehicle control, DOCA-salt, and DOCA-salt+OX1R-shRNA. DOCA-salt rats received subcutaneous implantation of a 21-day release, 75 mg DOCA pellet in addition to saline drinking water (1% NaCl, 0.2% KCl). DOCA-salt+OX1R-shRNA rats received bilateral microinjection of AAV2-OX1R-shRNA into the paraventricular nucleus (PVN) to knockdown function of the Orexin 1-Receptor (OX1R) within that area. Following 2-weeks to allow full transgene expression, a DOCA pellet was administered in addition to saline drinking solution. Vehicle controls received sham DOCA implantation but were given normal water. During the 3-week DOCA-salt or sham treatment period, mean arterial pressure and heart rate were monitored utilizing tail-cuff plethysmography. Following the 3-week period, rat brains were collected for either PCR mRNA analysis, as well as immunostaining. Plasma samples were collected and subjected to ELISA analysis. In line with our hypothesis, OX1R expression was elevated in the PVN of DOCA-salt treated rats when compared to controls. Furthermore, following chronic knockdown of OX1R, the hypertension development normally induced by DOCA-salt treatment was significantly diminished in the DOCA-salt+OX1R-shRNA group. A concurrent reduction in PVN OX1R and AVP mRNA was observed in concert with the reduced blood pressure following AAV2-OX1R-shRNA treatment. Similarly, plasma AVP concentrations appeared to be reduced in the DOCA-salt+OX1R-shRNA group when compared to DOCA-salt rats. These results indicate that orexin signaling, specifically through the OX1R in the PVN are critical for the onset and maintenance of hypertension in the DOCA-salt model. This relationship is mediated, at least in part, through orexin activation of AVP producing neurons, and the subsequent release of AVP into the periphery. Our results outline a promising mechanism underlying the development of salt-sensitive hypertension through interactions with the brain orexin system.